Clinical Experience with α-Particle–Emitting (211)At: Treatment of Recurrent Brain Tumor Patients with (211)At-Labeled Chimeric Antitenascin Monoclonal Antibody 81C6 - Zalutsky, Michael R. (2007)
α-Particle–emitting radionuclides, such as (211)At, with a 7.2-h half-life, may be optimally suited for the molecularly targeted radiotherapy of strategically sensitive tumor sites, such as those in the central nervous system. Because of the much shorter range and more potent cytotoxicity of α-particles than of β-particles, (211)At-labeled agents may be ideal for the eradication of tumor cells remaining after surgical debulking of malignant brain tumors. The main goal of this study was to investigate the feasibility and safety of this approach in patients with recurrent malignant brain tumors. METHODS: Chimeric antitenascin monoclonal antibody 81C6 (ch81C6) (10 mg) was labeled with 71–347 MBq of (211)At by use of N-succinimidyl 3-[(211)At]astatobenzoate. Eighteen patients were treated with (211)At-labeled ch81C6 ((211)At-ch81C6) administered into a surgically created resection cavity (SCRC) and then with salvage chemotherapy. Serial γ-camera imaging and blood sampling over 24 h were performed. RESULTS: A total of 96.7% ± 3.6% (mean ± SD) of (211)At decays occurred in the SCRC, and the mean blood-pool percentage injected dose was ≤0.3. No patient experienced dose-limiting toxicity, and the maximum tolerated dose was not identified. Six patients experienced grade 2 neurotoxicity within 6 wk of (211)At-ch81C6 administration; this neurotoxicity resolved fully in all but 1 patient. No toxicities of grade 3 or higher were attributable to the treatment. No patient required repeat surgery for radionecrosis. The median survival times for all patients, those with glioblastoma multiforme, and those with anaplastic astrocytoma or oligodendroglioma were 54, 52, and 116 wk, respectively. CONCLUSION: This study provides proof of concept for regional targeted radiotherapy with (211)At-labeled molecules in oncology. Specifically, the regional administration of (211)At-ch81C6 is feasible, safe, and associated with a promising antitumor benefit in patients with malignant central nervous system tumors.